2022
DOI: 10.4049/jimmunol.208.supp.114.16
|View full text |Cite
|
Sign up to set email alerts
|

Bystander CD8 T cell memory responses partially protect mice against lethal vaginal HSV-2 challenge

Abstract: Herpes Simplex Virus type-2 (HSV-2) infection is one of the most prevalent sexually transmitted infections, yet no vaccine is currently available. Detailed analysis of HSV-infected human tissue revealed tissue-resident CD8 T cells (TRM) limit the duration and severity of HSV-2 episodes. Interestingly, recent studies indicate that the sensing and alarming function of CD8 TRMs is not restricted to cognate antigen interaction, but CD8 TRM can mediate protection against antigenically unrelated pathogens, termed “b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indeed, it was shown that a subset of vaginal CD8 T cells which were unspecific to the HSV antigen used for immunization, could play a partial role in genital protection. In this HSV challenge model, both peripheral CD8 T cells able to migrate to inflamed vaginal tissue and vaginal CD8 Trm of irrelevant antigen specificity were involved in this innate-like function (24).…”
Section: Characterization and Features Of Trm At Mucosal Surfacesmentioning
confidence: 91%
“…Indeed, it was shown that a subset of vaginal CD8 T cells which were unspecific to the HSV antigen used for immunization, could play a partial role in genital protection. In this HSV challenge model, both peripheral CD8 T cells able to migrate to inflamed vaginal tissue and vaginal CD8 Trm of irrelevant antigen specificity were involved in this innate-like function (24).…”
Section: Characterization and Features Of Trm At Mucosal Surfacesmentioning
confidence: 91%